Right Hemicolectomy in a Patient with Heterotaxy Syndrome - Maxime Dewulf; Roel Beckers; Pieter Pletinckx (World Journal of Colorectal Surgery)
In this communication, we present a first description of right hemicolectomy in a patient with heterotaxy syndrome (HS). A 78-year-old male was admitted to the outpatient clinic with complaints of dysphagia. Diagnostic workup revealed the presence of an esophageal web. On subsequent colonoscopy, a tumoral lesion was found in the ascending colon. Computed tomography scan illustrated abdominal situs ambiguous with right-sided polysplenia, right-sided stomach, and intestinal nonrotation. Furthermore, a preduodenal portal vein, azygos continuation of the inferior vena cava, and hemiazygos continuation of the left renal vein were observed. After careful assessment of the anatomy, a right hemicolectomy with radical lymphadenectomy was performed. HS consists of a rare and complex situs anomaly, with an abnormal arrangement of the thoracic and/or abdominal organs along the left–right axis. To our knowledge, right hemicolectomy has not been described in patients with HS.